2018
DOI: 10.1007/978-3-319-91287-5_2
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Cytochrome-C-Oxidase Account for Changes in Attenuation of Near-Infrared Light in the Healthy Infant Brain

Abstract: A novel multi-wavelength broadband near infrared spectroscopy (NIRS) system has been employed to simultaneously measure haemodynamic changes alongside changes in cellular oxygen utilization by measurement of oxidation state of mitochondrial enzyme cytochrome-c-oxidase (oxCCO). The aim of this study was to investigate the role of oxCCO in neural responses to functional activation in infants. Studies were performed using a NIRS broadband system in 33 typically developing infants aged between 4 and 6 months. Resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The choice of the number of wavelengths should be based on the clinical application sought, because for detecting crSO 2 changes in hypoxia or hypercapnia conditions numerous wavelengths were not required. 37 In patients with conjugated hyperbilirubinemia, NIRS devices with more wavelengths provided higher crSO 2 values reducing bilirubin interference. 38,39 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the number of wavelengths should be based on the clinical application sought, because for detecting crSO 2 changes in hypoxia or hypercapnia conditions numerous wavelengths were not required. 37 In patients with conjugated hyperbilirubinemia, NIRS devices with more wavelengths provided higher crSO 2 values reducing bilirubin interference. 38,39 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing the number of wavelengths led to more complex algorithms, greater difficulty in signal processing and, in the end, more sophisticated and expensive devices. The choice of the number of wavelengths should be based on the clinical application sought, because for detecting crSO2 changes in hypoxia or hypercapnia conditions numerous wavelengths were not required 36 . In patients with conjugated hyperbilirubinemia, NIRS devices with more wavelengths provided higher crSO2 values reducing bilirubin interference 37,38 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the present study, we used a multichannel BNIRS system, which has been developed to specifically measure oxCCO (e.g., Phan et al, 2016) and has been shown to successfully isolate its signal (based on the absorption characteristics of oxCCO, which has a broad peak at 830 nm) from other chromophores (HHb and HbO 2 ), as described here (Siddiqui et al, 2018). The instrument has 4 source and 10 detector fibers (optodes) and a sampling rate of 1 s. The detectors were arranged in rows of five with the four sources between them (source detector separation was 30 mm), resulting in 16 measurement channels.…”
Section: Bnirs Methodologymentioning
confidence: 99%
“…This system has been used in a wide variety of research papers and was one of the first portable broadband systems capable of measuring oxCCO in a clinical setting, first described in 2014 [ 14 ]. miniCYRIL [ 36 ] is a miniature version of CYRIL, designed to be more portable so it can measure a wider variety of tasks in different settings. It comprises a miniature white light source, a customized miniature spectrometer, fiber-optic cables and a laptop for real-time visualization of results.…”
Section: Instrumentationmentioning
confidence: 99%